Preventing dysfunctional conflict: examining the relationship between different types of managerial conflict in venture capital-backed firms. Issue 4 (1st October 2016) - George, Bradley; Erikson, Truls; Parhankangas, Annaleena
Abstract: Prior literature reports mixed results relative to the performance outcomes of different types of conflict in top management teams. These conflicting results may stem from the complex interactions between different types of conflict. To address this gap in existing knowledge, we set out to explore the interactions between task, process, and affective conflict in entrepreneurial teams of venture-backed firms. Our data are based on a survey among 240 firms that received investment from Norwegian venture capital funds with a response rate of 25% (59 firms). Our results show that task conflict is positively related to affective conflict and that this relationship is partially mediated by process conflict. Furthermore, we find that team size moderates the relationship between task and process conflict. Our results provide a potential explanation for the previously reported inconsistent results on the outcomes of different types of conflict and suggest that especially nascent entrepreneurs with small management teams should be wary of all types of conflict – also those labeled as 'functional' by the prior literature.